2020
DOI: 10.1111/epi.16768
|View full text |Cite
|
Sign up to set email alerts
|

In vivo γ‐aminobutyric acid increase as a biomarker of the epileptogenic zone: An unbiased metabolomics approach

Abstract: ObjectiveFollowing surgery, focal seizures relapse in 20% to 50% of cases due to the difficulty of delimiting the epileptogenic zone (EZ) by current imaging or electrophysiological techniques. Here, we evaluate an unbiased metabolomics approach based on ex vivo and in vivo nuclear magnetic resonance spectroscopy (MRS) methods to discriminate the EZ in a mouse model of mesiotemporal lobe epilepsy (MTLE).MethodsFour weeks after unilateral injection of kainic acid (KA) into the dorsal hippocampus of mice (KA‐MTLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Although it may lead to partial volume effects in the slice thickness direction, this choice impacted both KA-MTLE and sham animals similarly. Our investigation did not include functional MRI 47,48 or MR spectroscopy (eg, glutamate, γ-aminobutyric acid [GABA] 49 ), two important approaches generating potentially complementary information. Furthermore, the diffusion acquisition protocol used could be refined to analyze fractional anisotropy of diffusion kurtosis.…”
Section: Study Limitations and Conclusionmentioning
confidence: 99%
“…Although it may lead to partial volume effects in the slice thickness direction, this choice impacted both KA-MTLE and sham animals similarly. Our investigation did not include functional MRI 47,48 or MR spectroscopy (eg, glutamate, γ-aminobutyric acid [GABA] 49 ), two important approaches generating potentially complementary information. Furthermore, the diffusion acquisition protocol used could be refined to analyze fractional anisotropy of diffusion kurtosis.…”
Section: Study Limitations and Conclusionmentioning
confidence: 99%
“…38 In magnetic resonance spectroscopy, an increase of GABA was seen in the epileptic hippocampus of an animal model. 39 Our findings add to the field that sprouted MFs impinge on inhibitory interneurons and that the inhibitory axonal endings outnumber the newly created MF boutons, which might possibly result in hippocampal hyperinhibition. This hyperinhibition might be worsened by the loss of hilar mossy cells, 40 which deprive granule cells of their excitation.…”
Section: Discussionmentioning
confidence: 54%
“…Searching for excitatory or inhibitory neurotransmitters, it was shown in patients analyzed with stereoencephalographic electrodes in addition to microdialysis probes that glutamate levels were elevated in both the epileptic neocortex and the hippocampus, whereas GABA and glutamine levels remained equal 38 . In magnetic resonance spectroscopy, an increase of GABA was seen in the epileptic hippocampus of an animal model 39 …”
Section: Discussionmentioning
confidence: 99%
“…95 Another advantage is the possibility of analyzing tiny spatial tissue regions, allowing a direct characterization of the metabolite in question that can be concealed in large sampling tissue mass. For example, a recent ex vivo HR-MAS study 96 of epilepsy with a kainate-injected epileptic mouse model reported an increased -aminobutyric acid (GABA) level in the entire ipsilateral anterior region of the hippocampus, eliciting the relevancy of GABA as a biomarker of the epileptogenic zone. However, the extensive sampling tissue mass (5 mg) made it impossible to delineate further the epileptic zone within the region.…”
Section: Technical Developmentsmentioning
confidence: 99%